If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -4(2x + 3) = 2x + 6(8x + 2) Reorder the terms: -4(3 + 2x) = 2x + 6(8x + 2) (3 * -4 + 2x * -4) = 2x + 6(8x + 2) (-12 + -8x) = 2x + 6(8x + 2) Reorder the terms: -12 + -8x = 2x + 6(2 + 8x) -12 + -8x = 2x + (2 * 6 + 8x * 6) -12 + -8x = 2x + (12 + 48x) Reorder the terms: -12 + -8x = 12 + 2x + 48x Combine like terms: 2x + 48x = 50x -12 + -8x = 12 + 50x Solving -12 + -8x = 12 + 50x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-50x' to each side of the equation. -12 + -8x + -50x = 12 + 50x + -50x Combine like terms: -8x + -50x = -58x -12 + -58x = 12 + 50x + -50x Combine like terms: 50x + -50x = 0 -12 + -58x = 12 + 0 -12 + -58x = 12 Add '12' to each side of the equation. -12 + 12 + -58x = 12 + 12 Combine like terms: -12 + 12 = 0 0 + -58x = 12 + 12 -58x = 12 + 12 Combine like terms: 12 + 12 = 24 -58x = 24 Divide each side by '-58'. x = -0.4137931034 Simplifying x = -0.4137931034
| 14+9x=5x+62 | | 10x+13=34-12x | | 9f=7f-14 | | 33x-8=7 | | Y=21x+7 | | 4x/3=3x-5/2 | | 2x+20=25-9x | | 25x+10=58 | | 2x-7-4x+3=2x-4x-7 | | 6z^2+3=729 | | 123/3 | | 15-t+8y=-13 | | 4/13/6.5 | | x^2(x-13)-2(2x-7)= | | (4x+1)+(11+2x)=90 | | 6=48/x | | -19-2c=-c | | 64w-56w=56w | | (4x+1)+(11+2)=90 | | 2-14/-4 | | X/12=7/8 | | 35x+y+15=180 | | 2u+11=37 | | -3x/2=7/8 | | 9x+7b=267000 | | v^2=52 | | ((x^2)-(2x))-9=0 | | 28=5w-12 | | C=5+ab | | 292-200/4=x | | 7x-6x+8x=24 | | 3r^2-2=52.18 |